Jupiter and How to Observe It - McAnally, John W. (Astronomers' Observing Guides, 2008)
Jupiter is one of the most spectacular observing targets for amateur astronomers. There are various books about observing the planets, and several about Jupiter itself, but this is the only book to deal with the giant planet - its formation, structure, and incredible physics - as well as with the practical aspects of observation of the planet and its moons. The concept of the book - and of the series - is to present an up-to-date detailed physical and astrophysical description (part one); and then (part two) to consider how best to observe and image the giant planet. Jupiter and How to Observe It is a mine of information for all levels of amateur observers, from the beginning to the experienced, and will be fascinating reading for all practical amateur astronomers.